Performance of Three Mortality Prediction Scores and Evaluation of Important Determinants in Eight Pediatric Intensive Care Units in China - Zhang, Zhengzheng; Huang, Xiangyuan; Wang, Ying; Li, Ying; Miao, Hongjun; Zhang, Chenmei; Pan, Guoquan; Zhang, Yucai; Zhu, Xiaodong; Chen, Weiming; Li, Juanzhen; Su, Dongni; et al. (Frontiers in Pediatrics, 2020)
Background: The mortality predictions scores were widely used in pediatric intensive care units. However, their performances were unclear in Chinese patients and there were also no reports of large sample size in China. We evaluated the performances of three existing severity assessment scores in predicting PICU mortality and to identify important determinants. Methods: This prospective observational cohort study was carried out in eight multidisciplinary, tertiary-care PICUs of teaching hospitals in China. All consecutive patients admitted to the PICUs between Aug 1, 2016 and Jul 31, 2017 were included for analysis. We calculated PCIS, PRISM IV, PELOD-2 scores based on patient data collected in the first 24 hours after PICU admission. The in-hospital mortality was defined as all-cause death within three months after admission. The discrimination power was assessed using the area under the receiver-operating characteristics (ROC) curve (AUC) and calibration using the Hosmer-Lemeshow goodness-of-fit test. Results: A total of 4770 eligible patients were recruited (median age 18.2 months, overall mortality rate 4.7%, median length of PICU stay 6 days). The AUC (95% confidence intervals, CI) were 0.76 (0.70-0.78), 0.76 (0.72-0.80) and 0.80 (0.76-0.84) for PCIS, PRISM IV and PELOD-2, respectively. The Hosmer-Lemeshow test gave a chi-square of 3.16 for PCIS, 2.16 for PRISM IV and 4.81 for PELOD-2 (P ≥ 0.19). Cox regression identified five predictors from the items of scores better associated with higher death risk, with C-index of 0.82 (95%CI 0.79-0.86), including higher platelet (HR=1.85, 95% CI 1.59-2.15), invasive ventilation (HR=1.41, 1.27-1.56)and pupillary light reflex (HR=1.31, 95% CI 1.21-1.41) scores, lower pH (HR 0.89, 0.84-0.93) and lower PaO2 (HR 0.91, 0.86-0.96) scores. Conclusions: Performances of the three scores in predicting PICU mortality are comparable, and five predictors were identified with better prediction to PICU mortality in Chinese patients.